STREAMLINING EMERGENCY DEPARTMENT EFFICIENCY: IMPLEMENTING BUSINESS PROCESS RE-ENGINEERING TO REDUCE PATIENT WAIT TIMES - TRIANA, I KETUT DIAN LANANG; Agustina, Putu Dyah Candra; Febrian, Rivaldi; Wiadnya, I Dewa Gede Putra; Paramarta, Vip (Universitas Islam Negeri Alauddin Makassar, 2024)
Background: The Emergency Department (ED) plays vital roles in delivering emergency services for various clinical conditions. ED is required to provide health services even under high environmental pressures, such as overflowing patients, to speed up responsiveness. Therefore, efficiency should be a matter of concern in ED. The implementation of Business Process Re-Engineering (BPR) could significantly increase ED efficiency, specifically by reducing patient wait times. Objective: This study aims to review the relevant literature correlated to BPR and identify its roles in order to increase efficiency from the wait times. Method: We conducted a literature review with its reliable and replicable research protocol, which allowed the researchers to extract articles from PubMed, ProQuest and Google Scholars in recent 5 years using specific key words. The full text of relevant articles is then thematically synthesized and presented. Results: Our findings revealed that BPR implementation could affect the patients’ wait time reduction significantly by performing several procedures, such as applying Internet of Things (IoT) procedures, new layout design, staff allocation, applying heuristics method, simulation or event modelling procedures, and the technologies intervention. Conclusion: The BPR implementation has the potential to improve efficiency in the ED. However, it should be noted that the implementation of BPR needs to consider the ED necessity and a proper integration through existing health systems.